Wealth Maximization and the Cost of Capital: A Comment - Edwards, J. S. S.; Keen, M. J. (Quarterly Journal of Economics, 1984)
J. S. S. Edwards, M. J. Keen; Wealth Maximization and the Cost of Capital: A Comment*, The Quarterly Journal of Economics, Volume 99, Issue 1, 1 February 1